Women's education and the achievement of learning cities in Lagos, Nigeria - Amusa, Dare Rilwan (Tudásmenedzsment, 2022)
The study sought to examine how women's education can be harnessed to achieve learning cities in Lagos state. The essay evaluates the influence of women's education on the achievement of learning cities in Lagos; finds out how to improve the participation in women's education; examines the form of women's education useful to achieve learning cities in Lagos state and assesses how learning cities can be achieved with women education. Three research questions were raised and answered by the essay. Findings of the study showed that to improve the patronage of women's education in Lagos state, there should be opportunities for women to have basic education, learning programs should be divided into sections (morning, afternoon, and evening), women should be allowed to choose their desire vocations, learning should be made free and accessible and inclusive for all gender and the study recommended that to achieve the learning city in Lagos through women education, there should be opportunities for all women to partake in basic education at their leisure time and their convenient time; women should be given opportunity to learn various entrepreneurship skills or trade as this would enhance their thinking skills and develop them economically and there should be a provision of employment opportunity for women to encourage the non-literate and the potential literate as a result of the new normal.